2015
DOI: 10.1186/s40659-015-0059-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization (IVF) in mammals: epigenetic and developmental alterations. Scientific and bioethical implications for IVF in humans

Abstract: The advent of in vitro fertilization (IVF) in animals and humans implies an extraordinary change in the environment where the beginning of a new organism takes place. In mammals fertilization occurs in the maternal oviduct, where there are unique conditions for guaranteeing the encounter of the gametes and the first stages of development of the embryo and thus its future. During this period a major epigenetic reprogramming takes place that is crucial for the normal fate of the embryo. This epigenetic reprogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 215 publications
(201 reference statements)
4
82
0
1
Order By: Relevance
“…Factors known to be different between IVF and natural development can cause epigenetic influence, including techniques, embryo culture media and environmental exposures such as tissue culture plastics (Ventura-Junca et al 2015). Bisphenol A (BPA) is known for its action as an endocrine-disrupting compound and a weak estrogen agonist/antagonist.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…Factors known to be different between IVF and natural development can cause epigenetic influence, including techniques, embryo culture media and environmental exposures such as tissue culture plastics (Ventura-Junca et al 2015). Bisphenol A (BPA) is known for its action as an endocrine-disrupting compound and a weak estrogen agonist/antagonist.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…Our procedure allows repeated testing over an extended time-span of many years following sample collection, especially because it has been demonstrated that methylation of sperm DNA is not subject to change over time (14). Since assisted fertilization techniques have increasingly shown problems arising after a significant time-span (15), it becomes increasingly important to monitor the methylation status of germ cell genes.…”
Section: Resultsmentioning
confidence: 99%
“…The altered methylations of the endothelial nitric oxide synthase (eNOS) gene leads to decreased vascular NO synthesis in the aorta, and endothelial dysfunction and increased stiffness lead to arterial hypertension (23,24). Exogenous Gonadotropins administered to the ovary during controlled ovarian stimulation causes epigenetic changes in peg1, kcnq1ot1, zac (Zac1), and h19 (25). Zac1 plays an important role in neural stem cell quiescence, proliferation and differentiation (26).…”
Section: Discussionmentioning
confidence: 99%